Podcast-Based Learning Video on Cultural Diversity in Indonesian for Fourth-Grade Social Studies - Ni Putu Jayanti Dian Pratiwi; I Gusti Agung Ayu Wulandari; I Gede Astawan (Jurnal Pendidikan Multikultural Indonesia, 2025)
Social studies learning in elementary schools is still predominantly dominated by lecture methods and textbook-based instruction, which limits students’ engagement and reduces meaningful learning experiences. This condition contributes to students’ low understanding of the topic “Cultural Diversity of My Nation” and their limited active participation in the learning process. This study aimed to analyze, develop, and evaluate the validity, practicality, and effectiveness of podcast-based instructional videos on the topic of cultural diversity in elementary social studies learning. The research employed a Research and Development approach using the ADDIE model. The participants consisted of three expert validators, including a content expert, an instructional design expert, and a media expert, as well as 22 elementary school students. Data were collected through questionnaires and achievement tests. The questionnaires were used to assess media validity and practicality, while the tests measured learning effectiveness. Data were analyzed using descriptive quantitative, qualitative techniques, and t-test analysis. The findings indicated that the podcast-based instructional video demonstrated very high validity, strong practicality, and significant effectiveness in improving students’ conceptual understanding. Conceptually, the media promotes interactive learning, supports student autonomy, and enhances engagement in understanding cultural diversity.